Outcome of Percutaneous Nephrolithotomy in Horseshoe Kidneys - Singh Dongol, Udaya Man; Bohora, Sandeep (Journal of Lumbini Medical College, 2018)
Introduction: The horseshoe kidney is extremely rare, the incidence being one in every 400 - 800 patients. In a recent review of more than 15000 radiographic imaging studies, the incidence was one in every 666 patients. The renal stone formation in horseshoe kidney is around 20-80%. Percutaneous nephrolithotomy is the most accepted modality of treatment . This study was carried out to find the outcome of percutaneous nephrolithotomy in horseshoe kidneys.Methods: Between May 2013 and November 2017, 11 adult patients (12 renal units) with stones in horseshoe kidneys underwent percutaneous nephrolithotomy in the department of urosurgery, Kathmandu Medical College and Teaching Hospital and were evaluated for the operating time, stone free rate , complications and hospital stay. Data analysis was done using Statistical Package for the Social sciences (SPSS) Version 20. Categorical data were analysed by using Fisher exact test.Results: The mean age of the patients was 30.9 years (SD = 10.3) and the mean stone burden was 385.83 mm2 (SD = 331.3). The overall stone free rate was 83.33%. The two patients with residual stones when counselled for Extracorporeal shock wave lithotripsy, refused for it and decided to be on follow up. No auxiliary procedure was done. The complications noted were of Clavien-Dindo grade I and II. No pleural or bowel injury was seen. One patient needed blood transfusion.Conclusions: Percutaneous nephrolithotomy is safe and effective in the management of stones in horseshoe kidneys. It does not carry increased risk than reported in normal kidneys.DOI: https://doi.org/10.22502/jlmc.v6i2.238